Temporospatial Flavonoids Metabolism Variation in Ginkgo biloba Leaves - Guo, Ying; Wang, Tongli; Fu, Fang-Fang; El-Kassaby, Yousry A.; Wang, Guibin (Frontiers in Genetics, 2020)
Ginkgo (Ginkgo Biloba L.) is a high-value medicinal tree species characterized by its flavonoids beneficial effects that are abundant in leaves. We performed a temporospatial comprehensive transcriptome and metabolome dynamics analyses of clonally propagated Ginkgo plants at four developmental stages (time: May to August) across three different environments (space) to unravel leaves flavonoids biosynthesis variation. Principal component analysis revealed clear gene expression separation across samples from different environments and leaf-developmental stages. We found that flavonoid-related metabolism was more active in the early stage of leaf development, and the content of total flavonoid glycosides and the expression of some genes in flavonoid biosynthesis pathway peaked in May. We also constructed a co-expression regulation network and identified eight GbMYBs and combining with other TF genes (3 GbERFs, 1 GbbHLH, and 1 GbTrihelix) positively regulated the expression of multiple structural genes in the flavonoid biosynthesis pathway. We found that part of these GbTFs expressions was negatively correlated with mean minimum temperature and mean relative humidity, while positively correlated with sunshine duration. This study increased our understanding of the molecular mechanisms of flavonoids biosynthesis in Ginkgo leaves and provided insight into the proper production and management of Ginkgo commercial plantations.